Algebra
posted by Kristi .
Find the difference quotient and simplify your answer. Step by step. f(x) = 3x2 − 6x, f(x + h) − f(x) h , h ‚ 0

f(x)=3x^26x
f(x+h)=3(x+h)^2 6(x+h)
= 3x^2+6xh+3h^26x6h
so f(x+h)f(x)= 0x^20x+6xh3h^26h
dividing that by h then
6x3h6
as h approaches zero, then the difference quotent= 6x6
Respond to this Question
Similar Questions

Math
Simplify: x4 −4x3 −27x+108  x3 −3x2 −16x+48 PLEASE! 
college
Evaluate the difference quotient for the given function. Simplify your answer. f(x) = 3 + 5x − x2, f(4 + h) − f(4) h 
Math
Find the augmented matrix for each of the following systems of linear equations: (a) 3x1 − 2x2 = −1 4x1 + 5x2 = 3 7x1 + 3x2 = 2 (b) 2x1 + 2x3 =1 3x1 − x2 + 4 x3 = 7 6x1 + x2 − x3 = 0 (c) x1 + 2x2 − x4 … 
biology
Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner? 
Math
Simplify the difference quotient [f(2 + h) − f(2)]/h if h ≠ 0. f(x) = x^2 − 3x I keep getting the answer wrong...please help. 
Mathematics
Simplify the difference quotient [f(x) − f(a]/[x − a] if x ≠ a. f(x) = SQROOT of (x − 27) (Hint: Rationalize the numerator.) 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and … 
math
An equation and the steps to solve it are shown below: 3x − one over two (8x − 2) = 4 Step 1: 3x − 4x + 1 = 4 Step 2: x + 1 = 4 Step 3: x + 1 − 1 = 4 − 1 Step 4: x = 3 Which step was the error made and … 
algebra
Below are the steps to solve an equation: Step 1: x − 2 + 3 = 7 Step 2: x − 2 = 7 − 3 Step 3: x − 2 = 4 Which of the following is a correct next step to solve the equation? 
MATH
Hannah is showing her work in simplifying (6.1 − 4.5) − 2.5 + 3.9. Identify any error in her work or reasoning. Step 1: (6.1 − 4.5) − 2.5 + 3.9 Step 2: 6.1 + (− 4.5 − 2.5) + 3.9 (associative property) …